ANALYSIS OF ELECTRICAL LOAD ASSESSMENT LSU (LAPAN SURVEILLANCE UAV) 03 - Setyadewi, Imas Tri; Sumarna, Encung; Prabowo, Yanuar (Indonesian Journal of Aerospace, 2019)
LSU 03 Aircraft was used for LSU MISI with capability cruise up to 340 km. LSU 03 has an operation for marine safety from illegal fishing. To support the monitoring mission of illegal fishing with operation range up to 250 km or 3 hours flight, several required system are needed such as autopilot system, datalink, propulsion, and payload. All of system then analysed by an ELA (Electrical Load Assessment) of the aircraft system to know the necessary power required to conduct the initial mission of the aircraft. ELA analysis is done by calculating the power requirement from each component specification and function test of the component for validation of calculation result. From the results of the study, the amount of power consumption is 35% from the spec calculation, which is 32.43 Wh which can be accommodated by a battery system up to 4.2 hours. Whereas for ignition or aircraft engines whose source of battery uses LIPO 2S 7.4 Vdc batteries can accommodate the ignition energy requirements for more than 11 hours.